The Structure of Cyclodecatriene Collinolactone, its Biosynthesis, and Semisynthetic Analogues: Effects of Monoastral Phenotype and Protection from Intracellular Oxidative Stress. Issue 43 (21st September 2021) - Schmid, Julian C.; Frey, Kerstin; Scheiner, Matthias; Garzón, Jaime Felipe Guerrero; Stafforst, Luise; Fricke, Jan‐Niklas; Schuppe, Michaela; Schiewe, Hajo; Zeeck, Axel; Weber, Tilmann; Usón, Isabel; Kemkemer, Ralf; et al.
Abstract: Recently described rhizolutin and collinolactone isolated from Streptomyces Gö 40/10 share the same novel carbon scaffold. Analyses by NMR and X‐Ray crystallography verify the structure of collinolactone and propose a revision of rhizolutin's stereochemistry. Isotope‐labeled precursor feeding shows that collinolactone is biosynthesized via type I polyketide synthase with Baeyer–Villiger oxidation. CRISPR‐based genetic strategies led to the identification of the biosynthetic gene cluster and a high‐production strain. Chemical semisyntheses yielded collinolactone analogues with inhibitory effects on L929 cell line. Fluorescence microscopy revealed that only particular analogues induce monopolar spindles impairing cell division in mitosis. Inspired by the Alzheimer‐protective activity of rhizolutin, we investigated the neuroprotective effects of collinolactone and its analogues on glutamate‐sensitive cells (HT22) and indeed, natural collinolactone displays distinct neuroprotection from intracellular oxidative stress. Abstract : Collinolactone shares the same carbon scaffold with rhizolutin and X‐ray crystallography has provided the absolute configuration. A highly non‐collinear gene cluster was identified. Studies of cell viability using fluorescence microscopy revealed that analogues of collinolactone induce the formation of a monopolar spindle phenotype while collinolactone showed neuroprotective effects by reducing intracellular oxidative stress.